Measurement and Prediction of Sawing Characteristics Using Dental Reciprocating Saws: A Pilot Study on Fresh Bovine Scapula - Dedong Yu; Fan Zou; Wenran Zhang; Qinglong An; Ping Nie (Lubricants, 2023)
Bone sawing is one of the most common operations during traditional dental and cranio-maxillofacial surgery and training systems based on virtual reality technology. It is necessary to predict and update conditions (including the sawing force, temperature and tool wear) in real time during VR surgical training and surgical simulation. All the specimens used in this study were fresh bovine scapula. The forces and temperatures were measured during the sawing process. Additionally, the thermal conductivity was measured via a laser flash instrument. Response surface methodology (RSM) was adopted to analyze and model the sawing force and sawing temperature. Meanwhile, tool wear was observed using a scanning electron microscope. The regression models of the sawing force and temperature rise under different experimental conditions were acquired. To obtain the minimum force within the recommended parameter ranges of commonly used medical reference parameters for bone sawing, a higher rotational speed combined with a lower feed rate were recommended. When considering the sawing force and temperature rise comprehensively, the rotational speed should not be extremely high (about 13,000 rpm is recommended). Meanwhile, abrasive wear is the main wear mode of saw blades. In order to avoid surgery failure, it is necessary to replace the saw blade in time. The experimental data were confirmed to be scientific and accurate for the predicted models of sawing conditions. To minimize the main cutting force, a feed rate of 40 mm/min combined with a rotational speed of 13,700 rpm is recommended. High cutting temperatures have the potential to cause irreversible tissue damage, so surgeons using dental reciprocating saws need to avoid excessively high-speed gears.